Textural complexity and geochemistry of the last millennium pyroclastic deposits from Puyehue-Cordón Caulle Volcanic Complex - Walter Alexis Alfonzo; Romina Daga; Alejandro Demichelis; Gastón Goldmann; Sergio Ribeiro Guevara (Volcanica)
The component variability in Puyehue-Cordón Caulle Volcanic Complex (PCCVC) products reflects the inherent complexity of volcanic processes. We examine pyroclastic deposits from Cordón Caulle (2011 and 1960 eruptions) and Puyehue (MH tephra) in a profile ∼20 km windward of the PCCVC. All levels have comparable components (pumice, scoria, glass shards, crystals), but their proportions vary according to the dominant eruptive style in both vent sources. The particle microtextures combined with mineralogy and geochemistry differentiate juvenile from non-juvenile particles in macroscopically undifferentiated components, questioning prior assumptions. Highly vesicular pumice is the dominant juvenile component indicating decompression-driven gas exsolution processes. Juvenile blocky glass shards/obsidians, frequently associated with lithics, now provide insights into the potential higher involvement of magma in the phreatomagmatic phases of the MH deposit. Nevertheless, the variability of tephra components is a characteristic of the PCCVC, regardless of the juvenile or lithic character. This research refines tephrochronological tools and deepens our understanding of volcanic processes and deposits in the PCCVC.